Numerical results on slip effect over an exponentially stretching/shrinking cylinder - Najib, Najwa; Bachok, Norfifah; Dzulkifli, Nor Fadhilah; Pop, Ioan (MDPI, 2022)
An investigation is conducted to study the flow and heat transfer on stagnation point over an exponentially stretching/shrinking cylinder filled with nanofluid in the presence of slip at the boundary. By using the appropriate exponential similarity transformation, the governing equations are converted into nonlinear ordinary differential equations and then solved computationally using bvp4c in Matlab software. The results of skin friction coefficient, heat transfer coefficient, velocity and temperature profiles on slip parameter, curvature parameter, nanoparticles as well as nanoparticle volume fraction parameter are presented graphically. The presence of slip and curvature parameters cause the region of dual solutions to expand and at once enhance the heat transfer rate at the surface but somehow the heat transfer rate at the surface decreases rapidly when cylinder is shrunk. The aim of this paper is to investigate the effect of slip parameter on nanofluid as well as on the stretching/shrinking surface. The new findings of the effects of skin friction and heat transfer coefficient on different nanoparticles and nanoparticle volume fraction were discussed. Since there are dual solutions in the flow characteristics, we carry out a stability analysis to verify which solution is in a stable state and can be realized physically.